Accessibility and Quality of Palliative Care—Experience in Primary Health Care - Viljaras Reigas; Ingrida Šukienė (Medicina)
Background and Objectives: Palliative care is a very important part of medicine, aimed at ensuring an improvement in quality of life and a reduction in distressing symptoms in patients with serious, incurable, progressive diseases. The issues of the accessibility and quality of these services should be a focus for health policymakers and researchers, although it is acknowledged that a significant portion of the public has not heard about this service. For this reason, it is important to investigate the experience of the accessibility and quality of palliative care services in primary healthcare facilities. Materials and Methods: A quantitative study was conducted in institutions providing outpatient and inpatient palliative care services. A total of 784 patients and 219 family members participated in the study. Participants expressed their opinions through a questionnaire containing 24 statements, to which they responded by indicating their level of agreement on a Likert scale. The collected data were analyzed using statistical analysis software. Results: Palliative care services are widely available in large cities, but their accessibility is very limited in small towns and rural areas. Patients and their families are not familiar with the concept of palliative care, often equating it with the provision of treatment and nursing services, and they see the support of clergy as unnecessary. Although patients and their families rate the quality of the services received positively, they note shortcomings related to communication among staff. Conclusions: Palliative care services are provided within the primary healthcare system by specialists with qualifications regulated by legislation; however, patients do not see the need to receive assistance from clergy members. Based on the study results, it can be concluded that in Lithuania, the accessibility of palliative care is ensured in larger cities but is insufficient in smaller towns and rural areas. Patients tend to rate indicators reflecting the quality of palliative care services positively; however, they are not convinced that these services improve their quality of life.